Nilai Tradisi sebagai Strategi: Kepemimpinan Minangkabau Universal dalam Dinamika Bisnis Keluarga - Chichi Andriani; Yunia Wardi; Susi Evanita (Jurnal Ecogen, 2025)
This study aims to analyze the role of Universal Minangkabau Leadership values ​​and their relevance in managing family businesses in West Sumatra, and to analyze the influence of Universal Minangkabau Leadership on employee performance. The data source for this study is primary data, namely questionnaires. The population in this study was all family businesses in West Sumatra, spread across 19 regencies/cities in West Sumatra. The sampling technique used purposive sampling based on the criteria of 1) being a family business, 2) having a business age of more than 3 years, and 3) having more than 5 employees. This resulted in a total sample of 240 family businesses. Data processing in this study was conducted using descriptive analysis techniques and multiple regression analysis. The results found that 1) the implementation of the four values ​​of Universal Minangkabau Leadership custom, religiosity, intellectuality, and transformational—by leaders was generally perceived positively by respondents and was deemed relevant in supporting the strategy and success of family business management in West Sumatra. 2) Traditional leadership, reflected through the application of the values ​​of custom-based leadership, religion-based leadership, and knowledge-based leadership, contributed significantly to improving employee performance. and 3) modern leadership reflected through transformational leadership has an influence on the performance of family business employees in West Sumatra.